Homeopathy Assessment—Contribution of the Human Sciences - Renoux, Hélène (Homeopathy, 2021)
The recent questions about homeopathy raised by some sceptics have focused an awareness on this therapy and led different protagonists among the scientific community to seek a much-needed re-assessment. The inputs coming from external but benevolent experts will broaden the knowledge and the consciousness of the whole medical community, and more widely of the public, about the meaning and the value of homeopathy.Looking at this from the point of view of the human sciences gives a perspective on the universality of the philosophy that underlies homeopathic thinking, which is particularly visible in the methodological similarities between homeopathic provings and sociological or anthropological observations. It also explains how this view of health and care coincides with the expectations of the public, who no longer want a limited mechanical approach to the human body or more generally to the environment.The input to homeopathy of the human sciences, with their methodological tools and approaches, and highlighting the possibilities offered by mixed-methods research, could enable these notions to be heard and shared in the wider scientific community.
Keywords: homeopathy assessment; qualitative studies; semi-structured interviews; homeopathic provings; sociological approach; mixed-method research; clinical trials